A Ação mediadora da educação: do discurso democrático à gestão autoritária - Weyne, Oswaldina Alcantara (1993)
This study is focused on comprehending the social politics of the state, starting from the military intervention (1964-1979), percieved through the technical planning that characterized it, and of the mediation that is explicit in its discourse of claiming to be democratic and of its authoritarian administration that takes its course in the middle of contradictions that impell the concrete historical movement of the Brazilian society. It doesn' t come to any original or final conclusions about the proposed theme, overall, it brings up old questions and inquiries that enables a perception of the limits and possibilities of the discourse of the state, especially of the educational politics of the 'abertura' (1980-1985). This paper looks into the educational practice, trying to comprehend and unveil the reality of the situation, centering its attention on the school of Ceará, beginning with its determining structures and conjunctures, going on to the more specific observation of the course taken by the educational politics, in relation to its functions with ampler connections ln the historical context of the Northeast in the Brazilian panorama.